A Phenomenological Study on the Antecedents and Consequences of Organizational Ostracism - Hasan TUTAR; Nuran ÖZTÜRK BAŞPINAR; Sevilay GÜLER (Anı Publishing, 2021)
Organizational environments are environments where conflicts of interest are intense due to business and human interactions. Various problems are experienced in these environments due to both business and human interaction and interpersonal relations. These problems cause various psychological and physical health problems in the employees and organizational health problems such as reduced job satisfaction and damage to work peace in organizations. This study examined the problem of "organizational ostracism," an example of negative behavior in organizations. The study discussed the causes of ostracism and its effects on the ostracized person. The study was designed according to the descriptive phenomenological pattern, one of the qualitative research designs. The sample of the study was determined according to the purposeful sampling technique. The study data were collected through in-depth interviews from 19 faculty members with different titles and positions working in various departments of public universities. The research results were presented and interpreted as "code," "sub-theme," and "main theme." At the end of the examination, organizational exclusion; It was understood that it was caused by jealousy, ethnic, political and trade union discrimination. The impact of organizational ostracism on the individual excluded; intention to quit, feeling of burnout, and psychosomatic disorders were grouped under the main themes. Findings showed that organizational ostracism harms organizational and individual performance. The research results show that ostracism is an important organizational behavior problem that disrupts organizational and individual health and job satisfaction.